Biotransformation of ferulic acid into vanillyl alcohol and vanillic acid employing thermophilic bacterium Caldimonas thermodepolymerans - Hrabalová, Vendula; Opial, Tomáš; Musilová, Jana; Sedlář, Karel; Obruča, Stanislav (Enzyme and microbial technology, 2024)
Caldimonas thermodepolymerans, a Gram-negative, moderately thermophilic bacterium, exhibits a remarkable biotechnological potential. Given the presence of genes in its genome dedicated to the metabolization of ferulic acid (FA), this study aimed to explore the bacterium's capability for biotransforming FA into high-value metabolites. The results unequivocally demonstrate the bacterium's proficiency in the efficient and rapid conversion of FA into vanillyl alcohol (VOH) and vanillic acid (VA). By manipulating key cultivation parameters, such as adjusting initial FA doses and varying cultivation periods, the product profile can be tailored. Higher initial doses and shorter cultivation periods favor the production of VOH, while lower FA doses and extended cultivation periods lead to the predominant formation of VA. Furthermore, the process can be operated in a repeated-batch scenario. This underscores the potential of C. thermodepolymerans for industrial biotransformation of FA, presenting a promising avenue for leveraging its capabilities in practical applications.
Keywords: biotransformace; průmyslová mikrobiologie; Biotransformation; Benzyl Alcohols; Caldimonas thermodepolymerans; benzylalkoholy; Vanillic acid; kyseliny kumarové; Coumaric Acids; Ferulic acid; kyselina vanilová; Vanillyl alcohol; Industrial Microbiology; Thermophiles; Vanillic Acid